Preparation method and application of crystallized red phosphorus nanosheet with monatomic shell layer

By photodeposition treatment of crystalline red phosphorus and precious metal salt solution, crystalline red phosphorus nanosheets with single atomic shell were prepared, which solved the slow carrier migration rate and fast recombination of red phosphorus-based photocatalytic materials in photocatalytic reactions. The problem of this paper realizes efficient photocatalytic hydrogen evolution reaction and promotes the large-scale application of materials.

CN119236979APending Publication Date: 2025-01-03NANKAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411333516.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing red phosphorus-based photocatalytic materials have problems such as slow carrier migration rate and fast recombination in photocatalytic reactions, which limits their wide application. Moreover, the preparation of high-dispersed single-atom catalysts is difficult and easy to agglomerate, which affects the scale of the material. .

Method used

A preparation method is adopted to mix crystalline red phosphorus with precious metal salt solution for photodeposition to form crystalline red phosphorus nanosheets with single atomic shells. The highly dispersed red phosphorus-loaded type is prepared by combining phosphorus oxidative bonds with metals. Material, used for photocatalytic hydrogen evolution reaction. The method includes mixing the crystalline red phosphorus preparation dispersion with the noble metal salt solution, photodeposition, filtration and vacuum drying to form a crystalline red phosphorus nanosheet of a single atomic shell.

Benefits of technology

It realizes a safe and efficient photocatalytic hydrogen evolution reaction, and the preparation process is simple and repetitive, which is conducive to the large-scale application of materials and improves the efficiency of photocatalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236979A_ABST
    Figure CN119236979A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a crystallized red phosphorus nanosheet with a monatomic shell layer, which comprises the following steps: preparing crystallized red phosphorus into a crystallized red phosphorus dispersion liquid, and adding a noble metal salt solution into the crystallized red phosphorus dispersion liquid to obtain a reaction dispersion liquid; carrying out heat preservation and photodeposition treatment on the reaction dispersion liquid to obtain a reacted dispersion liquid; and carrying out filtration and vacuum drying treatment on the reacted dispersion liquid to obtain the crystallized red phosphorus nanosheet with the monatomic shell layer. A series of high-dispersion red phosphorus supported materials with the monatomic shell layers are prepared, the safe and efficient crystalline red phosphorus nanosheets with the monatomic shell layers applied to photocatalytic hydrogen evolution reaction can be obtained, and the preparation process is simple and high in repeatability; the large-scale application of the crystallized red phosphorus nanosheet with the monatomic shell layer is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of phosphorus chemical materials, and in particular to a method for preparing a crystalline red phosphorus nanosheet having a single atomic shell and its application. Background Art

[0002] In recent years, red phosphorus has been widely used in photocatalytic research due to its narrow band gap, low cost and wide availability. Although amorphous red phosphorus has a narrow band gap and can respond to visible light, its shortcomings such as slow migration rate and fast recombination of photogenerated carriers limit its widespread application.

[0003] However, crystalline red phosphorus loaded with single atoms can regulate the defects of amorphous red phosphorus, such as slow carrier mobility and fast recombination. Therefore, it is urgent to develop a simple, safe and efficient red phosphorus-based photocatalytic material to enable the large-scale application of red phosphorus-based photocatalytic materials. Summary of the invention

[0004] In view of this, the purpose of the present application is to propose a preparation method and application of crystalline red phosphorus nanosheets with a single atomic shell.

[0005] Based on the above objectives, the present application provides a method for preparing crystalline red phosphorus nanosheets with a single atomic shell, comprising:

[0006] preparing a crystalline red phosphorus dispersion from crystalline red phosphorus, and adding a noble metal salt solution to the crystalline red phosphorus solution to obtain a reaction dispersion;

[0007] The reaction solution is subjected to heat preservation and photodeposition treatment to obtain a post-reaction dispersion;

[0008] The dispersion liquid after the reaction is filtered and vacuum dried to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0009] Furthermore, the photodeposition treatment time is 0.5 to 2 hours.

[0010] Furthermore, the solute of the noble metal salt solution is chloroplatinic acid, chloroauric acid or chloropalladic acid, and the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus is 0.5-3%.

[0011] Furthermore, the temperature of the reaction dispersion is 5-15°C.

[0012] Furthermore, the light source for the optical deposition process is a xenon lamp, the wavelength of the light is a full-band light in the range of 320 to 780 nanometers, and the optical power of the xenon lamp is 100-600 milliwatts per square centimeter.

[0013] Furthermore, the vacuum drying treatment is carried out for 12 hours at a temperature of 60°C.

[0014] Furthermore, the method further comprises:

[0015] placing the red phosphorus to be treated at 200° C. and performing hydrothermal treatment for 12 hours to obtain hydrothermally treated red phosphorus;

[0016] The red phosphorus after the hydrothermal treatment is naturally cooled, filtered and vacuum dried at 60° C. for 12 hours to obtain amorphous red phosphorus after the red phosphorus is cooled to natural temperature;

[0017] The amorphous red phosphorus is subjected to a crystallization treatment to obtain crystalline red phosphorus.

[0018] Furthermore, the crystallization treatment includes:

[0019] Grinding amorphous red phosphorus, placing the ground red phosphorus in 1,2-diaminopropane, and performing solvent thermal treatment at 200° C. for 12 hours to obtain a red phosphorus dispersion;

[0020] The red phosphorus dispersion is cooled naturally, filtered and vacuum dried at 60° C. for 12 hours after reaching the natural temperature to obtain crystalline red phosphorus.

[0021] Based on the same inventive concept, the present application also provides the use of crystalline red phosphorus nanosheets with a single atomic shell prepared by the method for preparing crystalline red phosphorus nanosheets with a single atomic shell as described above in a photocatalytic hydrogen evolution reaction.

[0022] Furthermore, the application of the above-mentioned crystalline red phosphorus nanosheets with a single atomic shell in a photocatalytic hydrogen evolution reaction includes:

[0023] Adding water into the reactor;

[0024] Coating a crystalline red phosphorus nanosheet having a single atomic shell on a reaction substrate, and placing the substrate in a reactor, with the side coated with the crystalline red phosphorus nanosheet having a single atomic shell facing a transparent panel of the reactor;

[0025] The transparent panel is arranged to face the light source, and the internal environment of the reactor is adjusted to reach the humidity condition for photocatalytic decomposition of water to produce hydrogen by adjusting the environment controller.

[0026] As can be seen from the above, the present application provides a method for preparing crystalline red phosphorus nanosheets with a single atomic shell, which comprises preparing crystalline red phosphorus into a crystalline red phosphorus dispersion, mixing the crystalline red phosphorus with a noble metal salt solution for photodeposition treatment, and then filtering and vacuum drying to obtain crystalline red phosphorus nanosheets with a single atomic shell; this preparation process utilizes highly dispersed phosphorus-oxygen chemical bonds (PO-) in the oxide layer at the edge of the crystalline red phosphorus, and utilizes mild light to in-situ photodeposit the noble metal, so that the metal and the phosphorus-oxygen bond are combined into POM (M: metal), thereby preparing a series of highly dispersed red phosphorus-loaded materials with a single atomic shell, which can not only obtain safe and efficient crystalline red phosphorus nanosheets with a single atomic shell for use in photocatalytic hydrogen evolution reactions, but also has a simple preparation process with high repeatability, which is conducive to the large-scale application of crystalline red phosphorus nanosheets with a single atomic shell. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the present application or related technologies, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 1 of the present application;

[0029] Figure 2 This is an atomic force microscope image of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 1 of the present application;

[0030] Figure 3 Spherical aberration transmission electron microscopy of the crystalline red phosphorus nanosheet with a single atomic shell prepared in Example 1 of the present application Figure 1 ;

[0031] Figure 4 Spherical aberration transmission electron microscope image of a crystalline red phosphorus nanosheet with a single atomic shell prepared in Example 1 of the present application Figure 2 ;

[0032] Figure 5 This is an element distribution analysis diagram of the single-atom-shell crystalline red phosphorus nanosheet prepared in Example 1 of the present application, in which P is a phosphorus atom, O is an oxygen atom, and Pt is a platinum atom;

[0033] Figure 6It is the X-ray near-edge absorption spectrum and the extended X-ray fine absorption spectrum of the single-atom shell crystalline red phosphorus nanosheet prepared in Example 1 of the present application. In the figure, the upper two figures are the X-ray near-edge absorption spectrum, the ordinate: absorption of irradiated light, the abscissa: irradiated light energy, the upper right figure is a partial enlargement of the upper left figure; the lower two figures are the extended X-ray fine absorption spectrum, the abscissa: bond length, the ordinate: Fourier transform, Pt Foil: platinum element, PtO2: platinum oxide, Pt 1.5 -CRP: crystalline red phosphorus nanosheets with a platinum to phosphorus mass ratio of 1.5%. The lower left figure shows the extended X-ray fine absorption spectra of platinum, platinum oxide and crystalline red phosphorus nanosheets in the same coordinate system. The lower right figure shows the fitting curve of the extended X-ray fine absorption spectrum of the crystalline red phosphorus nanosheets.

[0034] Figure 7 It is the fitting curve of the extended X-ray fine absorption spectra of platinum and platinum oxide;

[0035] Figure 8 is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 2 of the present application;

[0036] Fig. 9 is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 3 of the present application;

[0037] Fig.10 is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 4 of the present application;

[0038] Fig.11 is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 5 of the present application;

[0039] Fig.12 is an X-ray diffraction pattern of a single atomic shell crystalline red phosphorus nanosheet prepared in Example 6 of the present application;

[0040] Fig.13 This is the X-ray diffraction pattern of the crystalline red phosphorus nanosheet with a single atomic shell prepared in Example 7 of the present application. DETAILED DESCRIPTION

[0041] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0042] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the embodiments of the present application should be the usual meanings understood by people with ordinary skills in the field to which the present application belongs. The "first", "second" and similar words used in the embodiments of the present application do not represent any order, quantity or importance, but are only used to distinguish different components. "Including" or "comprising" and similar words mean that the elements or objects appearing in front of the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0043] Phosphorus is one of the most common and abundant elements on Earth, accounting for about 0.1% of the earth's crust. Phosphorus (P): Chemical element No. 15, in the third period of the periodic table, Group VA (commonly known as the nitrogen group elements), is of great significance in the fields of chemistry, physics, ecology and biology. Generally speaking, elemental phosphorus can be divided into various allotropes such as white phosphorus (α-, β-, γ-phases), black phosphorus (bulky black phosphorus crystals and few layers of black phosphorene), and red phosphorus (amorphous red phosphorus and crystalline red phosphorus). Among them, white phosphorus is the most active and is widely used in organic chemistry. Black phosphorus, similar to graphene, is a semiconductor with a layered wrinkled structure that can be stripped into single-layer or few-layer black phosphorene. At room temperature, the band gap of bulk black phosphorus is 0.3-2.0 eV (electron volt) (the band gap is adjustable with the number of layers) and has a high mobility (about 1000cm 2 V -1 S -1 ), and is often used in field effect transistors, photodetection, solar cells and photocatalysis. Compared with white phosphorus and black phosphorus, red phosphorus is the most widely used phosphorus element. Due to its low cost, non-toxicity, easy availability and stability, it is widely used in daily life and industrial production, such as flame retardancy, smoke signal, electrocatalysis and chemical analysis.

[0044] In recent years, red phosphorus has been widely used in photocatalytic research due to its narrow band gap, low cost and wide availability. Although amorphous red phosphorus has a narrow band gap and can respond to visible light, its shortcomings such as slow migration rate and fast recombination of photogenerated carriers limit its widespread application.

[0045] However, crystalline red phosphorus loaded with single atoms can regulate the defects of amorphous red phosphorus such as slow carrier mobility and fast recombination. At present, the preparation of highly dispersed single-atom catalysts has problems such as difficult preparation and easy agglomeration into particles. Therefore, it is urgent to develop a red phosphorus-based photocatalytic material that is simple to prepare, safe and efficient, so as to enable the large-scale application of red phosphorus-based photocatalytic materials.

[0046] Based on this, the present application proposes a method for preparing crystalline red phosphorus nanosheets with a single atomic shell, which utilizes highly dispersed phosphorus-oxygen chemical bonds (PO-) in the oxide layer at the edge of the crystalline red phosphorus, and utilizes mild light to in-situ photodeposit precious metals, so that the metal and phosphorus-oxygen bonds are combined into POM (M: metal), thereby preparing a series of highly dispersed red phosphorus-loaded materials with a single atomic shell. Not only can safe and efficient crystalline red phosphorus nanosheets with a single atomic shell be obtained for use in photocatalytic hydrogen evolution reactions, but the preparation process is simple and highly repeatable, which is conducive to the large-scale application of crystalline red phosphorus nanosheets with a single atomic shell.

[0047] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0048] Embodiment 1:

[0049] 100 mg (milligram) of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL (milliliter) of deionized water to obtain a red phosphorus dispersion. The temperature was set to 10°C and stirred at 600 rpm for 0.5 hour. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus being 1.5 wt%, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion. The xenon lamp (light wavelength 320-780 nanometers, light power 300 milliwatts per square centimeter) was turned on and stirred for 2 hours. The mixture was filtered and washed with a large amount of water. After vacuum drying at 60°C for 12 hours, crystalline red phosphorus nanosheets with a single atomic shell were obtained.

[0050] The obtained crystalline red phosphorus nanosheets with a single atomic shell were subjected to X-ray diffraction analysis to obtain an XRD spectrum, such as Figure 1 As shown in the figure, no obvious characteristic peaks of platinum particles and platinum oxide (i.e., platinum clusters) were found, only obvious characteristic peaks of crystalline red phosphorus were found, and excellent crystallinity was shown. Atomic force microscopy analysis was performed on the obtained crystalline red phosphorus nanosheets with single atomic shells, as shown in the figure. Figure 2 As shown, it was found that the thickness of the obtained crystalline red phosphorus nanosheets with a single atomic shell was about 4 nm (nanometer).

[0051] The characteristic peaks of Pt particles and clusters were not observed from the XRD spectrum. Therefore, the crystalline red phosphorus nanosheets with single atomic shells were analyzed by spherical aberration electron microscopy to observe whether they were single atoms. Figure 3 and Figure 4 As shown, Figure 3 Shown is a platinum atom, Figure 4 for Figure 3 In the enlarged image based on the data, no platinum clusters were found. That is, a single atomic layer of 1-3nm was found to grow at the edge of the material and was highly dispersed to form a single atomic shell. Through a spherical aberration electron microscope, we can see that Pt atoms are evenly dispersed at the edge of the red phosphorus, and a large number of single atoms form a shell structure.

[0052] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to elemental distribution analysis, such as Figure 5 As shown, the element distribution further verifies the formation of an oxygen and platinum shell at the edge of red phosphorus.

[0053] The coordination mode of platinum atoms in the obtained crystalline red phosphorus nanosheets with single atomic shells was analyzed by X-ray near-edge absorption spectroscopy and extended X-ray fine structure analysis, such as Figure 6 The above two figures (X-ray near-edge absorption spectra) show that the prepared Pt 1.5 The absorption edge threshold of -CRP is between the two and tends to be closer to the oxidized platinum end, so the valence state of the prepared platinum is between 0-+4, close to +4.

[0054] In addition, we use the Fourier transform of the R space to determine the coordination mode by expanding the X-ray fine structure, such as Figure 6 As shown in the lower left figure, by comparing platinum and platinum oxide, we found that the sample we prepared did not have the characteristic peak of platinum particles. The data was fitted, as shown in Figure 6 Bottom right and Figure 7 As shown, it can be seen that the platinum-oxygen bond length of the synthetic sample (i.e., crystalline red phosphorus nanosheets with a single atomic layer) is 2 angstroms, as shown in Table 1, which is highly identical to the bond length of PtO2. Therefore, the synchrotron radiation data were fitted and it was found that platinum coordinated with oxygen at the edge of red phosphorus to form a PO-Pt structure, further proving that the prepared substance is a red phosphorus nanosheet with a single atomic shell and that the single atoms in the shell are highly dispersed.

[0055] Table 1 Fitting parameters of each sample in the extended X-ray fine structure

[0056]

[0057] CN a : Coordination number; bond length; σ 2c : Debye-Waller factor; Internal potential correction; Rfactor: goodness of fit.

[0058] Based on this, the present application provides a method for preparing crystalline red phosphorus nanosheets with a single atomic shell. The obtained substance is a red phosphorus nanosheet with a single atomic shell and the single atoms in the shell are highly dispersed, which is conducive to the application in the photocatalytic reaction process. This preparation method is simple and has high repeatability, which is conducive to the large-scale application of crystalline red phosphorus nanosheets with a single atomic shell.

[0059] Embodiment 2:

[0060] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10°C, and the stirring was performed at 600 rpm for 0.5 h. According to the mass ratio of the metal in the precious metal salt solution to the crystalline red phosphorus being 0.5 wt%, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mW per square centimeter) was turned on. The mixture was stirred for 2 h, filtered and washed with a large amount of water, and vacuum dried at 60°C for 12 hours to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0061] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Figure 7 As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and excellent crystallinity was exhibited.

[0062] contrast Figure 8 and Figure 1 , the graphs are almost consistent. It can be seen that as the mass ratio of the metal in the precious metal salt solution to the crystalline red phosphorus decreases from 1.5 to 0.5, the crystallinity of the obtained crystalline red phosphorus nanosheets remains unchanged, and does not affect the crystallization performance of the crystalline red phosphorus nanosheets with a single atomic shell.

[0063] Embodiment 3:

[0064] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 2 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0065] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Figure 8 As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and excellent crystallinity was exhibited.

[0066] contrast Figure 8 and Fig. 9 , the graphs are almost consistent. It can be seen that as the mass ratio of the metal in the precious metal salt solution to the crystalline red phosphorus increases from 0.5 to 1.0, the crystallinity of the obtained crystalline red phosphorus nanosheets remains unchanged, and does not affect the crystallization performance of the crystalline red phosphorus nanosheets with a single atomic shell.

[0067] Embodiment 4:

[0068] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroauric acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 2 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0069] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Fig. 9 As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and excellent crystallinity was exhibited.

[0070] contrast Fig.10 and Figure 1 The graphs are almost the same. It can be seen that under the premise that the mass ratio of the metal in the precious metal salt solution to the crystalline red phosphorus is the same, changing the type of precious metal will keep the crystallinity of the crystalline red phosphorus nanosheets unchanged, and will not affect the crystallization performance of the crystalline red phosphorus nanosheets with a single atomic shell.

[0071] Embodiment 5:

[0072] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 1 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0073] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Fig.10As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and excellent crystallinity was exhibited.

[0074] contrast Fig.11 and Figure 1 The characteristic peaks of the graph are almost the same. It can be seen that the crystallinity of the crystalline red phosphorus nanosheets obtained by different photodeposition treatment times (i.e., stirring time) remains unchanged, and does not affect the crystallization properties of the crystalline red phosphorus nanosheets with a single atomic shell.

[0075] Embodiment 6:

[0076] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 15 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 1 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0077] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Fig.11 As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and crystallinity was exhibited, but the crystallization performance decreased.

[0078] contrast Fig.11 and Fig.12 It can be seen that as the temperature for preparing the red phosphorus dispersion increases from 10°C to 15°C, the crystallinity of red phosphorus decreases. This is because the increase in temperature causes its structure to collapse during the photodeposition process. Although crystalline red phosphorus can be obtained, its performance decreases, and the increase in temperature affects its crystallinity.

[0079] Embodiment 7:

[0080] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 5 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 1 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0081] The obtained crystalline red phosphorus nanosheets with single atomic shells were subjected to X-ray diffraction analysis, as shown in Fig.12 As shown, no obvious characteristic peaks of platinum particles and platinum oxide were found, only obvious characteristic peaks of crystalline red phosphorus were found, and good crystallinity was exhibited.

[0082] contrast Fig.11 and Fig.13 , almost the same. It can be seen that as the temperature of preparing the red phosphorus dispersion drops from 10°C to 5°C, the crystallinity of red phosphorus remains unchanged, and does not affect the crystallization performance of the crystalline red phosphorus nanosheets with a single atomic shell.

[0083] Embodiment 8:

[0084] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10 ° C, and the stirring was carried out at 600 rpm for 0.5 h. The chloroplatinic acid solution was added dropwise to the red phosphorus dispersion according to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus of 0.5 wt%, 1.0 wt%, and 1.5 wt%, respectively. The xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 1 h, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0085] The element content of the prepared crystalline red phosphorus nanosheets with a single atomic shell was analyzed, and the analysis results are shown in Table 2.

[0086] Table 2 Elemental content analysis of crystalline red phosphorus nanosheets with single atomic shell prepared in Example 8

[0087]

[0088] Example 8 In different experiments for preparing crystalline red phosphorus nanosheets with single atomic shells, chloroplatinic acid solutions of different mass ratios were used as noble metal salt solutions to prepare crystalline red phosphorus nanosheets with single atomic shells. Example 6 showed that 0.5wt%, 1wt%, and 1.5wt% noble metal salt solutions were all able to obtain crystalline red phosphorus nanosheets with single atomic shells. The metal mass ratio of the noble metal salt solution only affected the metal loading of the prepared crystalline red phosphorus nanosheets with single atomic shells, and was positively correlated with the metal mass ratio of the noble metal salt solution.

[0089] Embodiment 9:

[0090] 100 mg of the prepared crystalline red phosphorus powder was ultrasonically dispersed in 100 mL of deionized water, the temperature was set to 10 ° C, and the stirring was carried out at 600 rpm for 0.5 h. According to the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus, the chloroplatinic acid solution was added dropwise to the red phosphorus dispersion, and the xenon lamp (light wavelength 320-780 nm, light power 300 mw / cm 2 ), stirred for 0.5 h, 1 h, and 2 h, respectively, filtered and washed with a large amount of water, and dried in vacuum at 60 °C for 12 h to obtain crystalline red phosphorus nanosheets with a single atomic shell.

[0091] The element content of the prepared crystalline red phosphorus nanosheets with a single atomic shell was analyzed, and the analysis results are shown in Table 3.

[0092] Table 3 Elemental content analysis of crystalline red phosphorus nanosheets with single atomic shell prepared in Example 9

[0093]

[0094] Example 9 In different experiments for preparing crystalline red phosphorus nanosheets with single atomic shells, different stirring times (i.e., the duration of photodeposition treatment) were used in the photodeposition experiments to obtain crystalline red phosphorus nanosheets with single atomic shells. Example 7 shows that crystalline red phosphorus nanosheets with single atomic shells can be obtained with photodeposition treatment times of 0.5h, 1h and 2h.

[0095] The above Examples 1-9 all use different parameters affecting the experiment, and all produce crystalline red phosphorus nanosheets with single atomic shells, indicating that the preparation method of crystalline red phosphorus nanosheets with single atomic shells provided in the present application has good application effect and a simple process, which is conducive to large-scale promotion and application.

[0096] In some embodiments, the use of the above-mentioned crystalline red phosphorus nanosheets with a single atomic shell in a photocatalytic hydrogen evolution reaction includes:

[0097] Step S100, adding water into the reactor;

[0098] Specifically, 5-10 ml of water is added to the reactor. The water is deionized water, lake water, sea water, tap water, river water, stream water, well water, aquaculture wastewater, or secondary effluent from a water plant. No requirements are made on the water quality.

[0099] Step S200, coating a crystalline red phosphorus nanosheet having a single atomic shell on a reaction substrate, and placing the substrate in a reactor, with the side coated with the crystalline red phosphorus nanosheet having a single atomic shell facing a transparent panel of the reactor;

[0100] Specifically, 2-10 mg of crystalline red phosphorus nanosheets with a single atomic shell are uniformly coated on one side of the reaction substrate. The reaction substrate can be a glass sheet, a glass fiber sheet, a filter paper sheet, a polytetrafluoroethylene sheet or a carbon cloth. The catalyst can be coated by direct coating, dispersion in anhydrous ethanol and drying, or dispersion in deionized water and drying.

[0101] A reaction substrate coated with crystalline red phosphorus nanosheets having a single atomic shell is placed in the reactor, and the side coated with the crystalline red phosphorus nanosheets having a single atomic shell is arranged to face the transparent panel, so that light irradiated through the transparent panel can directly irradiate the catalyst. The reaction substrate can be placed in a suspended manner in the reactor, that is, the corner of the reaction substrate is connected to the transparent panel to suspend the reaction substrate. After the reaction substrate is placed, the reactor is reclosed.

[0102] Step S300, setting the transparent panel toward the light source, and adjusting the environment controller so that the internal environment of the reactor reaches the humidity condition for photocatalytic decomposition of water to produce hydrogen.

[0103] Specifically, the light source of the device for photocatalytically decomposing water to produce hydrogen is determined, that is, whether the light source is the sun or an electric lamp. After the light source is determined, the transparent panel of the reactor is set toward the light source, so that the light generated by the light source vertically illuminates the transparent panel.

[0104] The environmental controller is adjusted to vaporize the water in the reactor to produce water vapor, thereby increasing the humidity in the reactor to reach the humidity condition for photocatalytic decomposition of water to produce hydrogen, which is conducive to the photocatalytic decomposition of water to produce hydrogen.

[0105] Embodiment 10:

[0106] 5 mg of 1.5 mass content of platinum-loaded crystalline red phosphorus nanosheets with single atomic shells (hereinafter referred to as Pt 1.5 -CRP) was evenly coated on a 4 cm x 4 cm reaction substrate and placed in a reactor facing the light-transmitting panel of the reactor. 5 ml of deionized water was added to the reactor. The pressure was set to 80 kPa and the humidity was 40% with high-purity argon (purity greater than 99.99%). A 100 mW / cm2 full-band xenon lamp (320 nm-780 nm) was used to perform a photocatalytic water decomposition hydrogen production experiment. During the experiment, the average hydrogen production rate for 4 hours was 970.7 μmol·g -1 ·h -1 .

[0107] Embodiment 11:

[0108] The reaction substrate is not coated with any object and is placed in a reactor. 5 ml of deionized water is added to the reactor. The pressure is set to 80 kPa with high-purity argon (purity greater than 99.99%), the humidity is 40%, and a 100 milliwatt per square centimeter full-band xenon lamp (320 nanometers-780 nanometers) is used to carry out a photocatalytic water decomposition hydrogen production experiment. During the experiment, the average hydrogen production rate for 4 hours is 0.

[0109] By comparing the experimental results of Example 10 and Example 11, it was found that the crystalline red phosphorus nanosheets with a single atomic shell can greatly improve the hydrogen production efficiency in the photocatalytic water hydrogen production experiment. The crystalline red phosphorus nanosheets with a single atomic shell prepared by the above-mentioned method for preparing crystalline red phosphorus nanosheets with a single atomic shell have good catalytic hydrogen production effect, are safe and efficient, and are conducive to promotion and application.

[0110] In this embodiment, a photocatalytic water decomposition hydrogen production device is used so that the photocatalytic water decomposition hydrogen production reaction can be carried out under certain humidity conditions by utilizing light and crystalline red phosphorus nanosheets with single atomic shells to decompose water and produce hydrogen without adding sacrificial reagents. Because it utilizes the reaction between water vapor and crystalline red phosphorus nanosheets with single atomic shells, there is no requirement for water quality, which avoids wasting water resources while improving the practicability and applicability of the method, which is conducive to large-scale promotion and implementation.

[0111] Photocatalytic hydrogen evolution reaction experiments were carried out using crystalline red phosphorus nanosheets with single atomic shells and a photocatalytic water decomposition hydrogen production device. The hydrogen evolution efficiency was significantly improved, which is conducive to the promotion, preparation and application of crystalline red phosphorus nanosheets with single atomic shells.

[0112] It should be noted that the above describes some embodiments of the present application. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the above embodiments and still achieve the desired results. In addition, the processes depicted in the accompanying drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0113] Although the present application has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.

[0114] The embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing crystalline red phosphorus nanosheets having a single atomic shell, characterized in that: include: preparing crystalline red phosphorus into a crystalline red phosphorus dispersion, and adding a noble metal salt solution into the crystalline red phosphorus dispersion to obtain a reaction dispersion; Performing heat preservation and photodeposition treatment on the reaction dispersion to obtain a reaction dispersion; The dispersion liquid after the reaction is filtered and vacuum dried to obtain crystalline red phosphorus nanosheets with a single atomic shell.

2. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: The photodeposition treatment time is 0.5 to 2 hours.

3. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: The solute of the noble metal salt solution is chloroplatinic acid, chloroauric acid or chloropalladic acid, and the mass ratio of the metal in the noble metal salt solution to the crystalline red phosphorus is 0.5-3%.

4. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: The temperature of the reaction dispersion is 5-15°C.

5. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: The light source for the optical deposition process is a xenon lamp, the light wavelength is a full-band light in the range of 320 to 780 nanometers, and the light power of the xenon lamp is 100-600 milliwatts per square centimeter.

6. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: The vacuum drying process was performed for 12 hours at a temperature of 60°C.

7. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 1, characterized in that: Also includes: placing the red phosphorus to be treated at 200° C. and performing hydrothermal treatment for 12 hours to obtain hydrothermally treated red phosphorus; The red phosphorus after the hydrothermal treatment is naturally cooled, filtered and vacuum dried at 60° C. for 12 hours to obtain amorphous red phosphorus after the red phosphorus is cooled to natural temperature; The amorphous red phosphorus is subjected to a crystallization treatment to obtain crystalline red phosphorus.

8. The method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to claim 7, characterized in that: The crystallization treatment comprises: Grinding amorphous red phosphorus, placing the ground red phosphorus in 1,2-diaminopropane, and performing solvent thermal treatment at 200° C. for 12 hours to obtain a red phosphorus dispersion; The red phosphorus dispersion is cooled naturally, filtered and vacuum dried at 60° C. for 12 hours after reaching the natural temperature to obtain crystalline red phosphorus.

9. Use of the crystalline red phosphorus nanosheets with a single atomic shell prepared by the method for preparing crystalline red phosphorus nanosheets with a single atomic shell according to any one of claims 1 to 8 in a photocatalytic hydrogen evolution reaction.

10. The use of the crystalline red phosphorus nanosheets with a single atomic shell in a photocatalytic hydrogen evolution reaction according to claim 9, characterized in that: include: Adding water into the reactor; Coating a crystalline red phosphorus nanosheet having a single atomic shell on a reaction substrate, and placing the substrate in a reactor, with the side coated with the crystalline red phosphorus nanosheet having a single atomic shell facing a transparent panel of the reactor; The transparent panel is arranged to face the light source, and the internal environment of the reactor is adjusted to reach the humidity condition for photocatalytic decomposition of water to produce hydrogen by adjusting the environment controller.

Citation Information

Patent Citations

  • Preparation method and application of copper-doped nanoribbon crystal form red-phosphorescent light catalyst

    CN116510757A